The Effectiveness of Early Ambulation Against the Amount of Postpartum Hemorrhage in Independent of Midwifery Practice (IMP) Semarang - Triana Sri Hardjanti; Farida Sukowati; Runjati Runjati (Jurnal LINK, 2014)
The aim of this research is to evaluate the effectiveness of early ambulation on post partum hemorhage in independent of midwifery practice. The research was a quasi-experimental with two group post-test research design. The number of samples was 30 subjects. The early ambulation programs consists of lay aside - sit down position, and lay aside-sit down-stand up position for 1 to 2 hours. Post partum hemorhage was measured by counting the amount of bleeding during post partum. Afterwards, the data were analyzed using Mann Whitney test. The results showed that the average amount of bleeding within the experimental group decreased 6.33 cc after the early ambulation with lay aside - sit down position in the first and second hours as well as in the control group which declined 9.66 cc after the early ambulation lay aside-sit down-stand up position 1 hour to 2 hours. However, there was no significant diference between post partum hemorhage in the experimetal and the control group (z=1.131, p0.05). It can be concluded that either early ambulation with lay aside - sit down position or lay aside-sit down-stand up position for 1 hour to 2 can decrease post partum hemorhage.